Determinants of The Development of Small and Medium Industries and Their Development Strategies in Regencies and Cities in Jambi Province - Suhadi; Nurhayani; Muhammad Rachmad R (International Journal of Business, Economics, and Social Development, 2026)
Industrialization is a fundamental pillar in the structural transformation of the national and regional economies. As a developing country, Indonesia continues to strive to accelerate the industrialization process to increase economic added value, expand employment opportunities, and reduce dependence on the primary sector. This study aims to analyze the determinants of Small and Medium Enterprises (SMEs) development and formulate development strategies in districts/cities in Jambi Province for the 2020–2024 period. The variables analyzed include business capital, human resource (HR) quality, technology, market access, and product innovation, which contribute to SME development. The analytical method used is panel data regression with a Fixed Effect Model (FEM) approach to identify influential factors, and a Quantitative Strategic Planning Matrix (QSPM) to formulate and prioritize development strategies. The results show that all independent variables simultaneously have a significant effect on SME development. However, partially, technology, market access, and innovation significantly influence SME development, while business capital and HR quality do not. Furthermore, the coefficient of determination (R²) of 0.8036 indicates that the model is able to explain 80.36 percent of the variation in SME development. Based on the QSPM analysis, the priority strategy for SME development in Jambi Province is strengthening the business capacity of SMEs with the highest Total Attractiveness Score (TAS). The next strategies, in order, are improving human resource quality, utilizing technology and digitalization, increasing labor productivity, and developing markets.